After the first death - Cormier, Robert (New York Avon Books, 1979)
Events of the hijacking of a bus of children by terrorists seeking the return of their homeland are described from the perspectives of a hostage, a terrorist, an Army general involved in the rescue operation, and his son, chosen as the go-between.
Keywords: Terrorism -- Fiction; Fathers and sons -- Fiction